Unravelling the potential of disposable and modifiable pencils as catalyst supports for hydrogen evolution reaction. (22nd September 2022) - Paudel, Mohan; Daniels, Braydan; Arts, Amanda M.; Gupta, Alexander; Kalbfleisch, Theodore; Hofsommer, Dillon T.; Grapperhaus, Craig A.; Buchanan, Robert M.; Gupta, Gautam
Abstract : Pencil substrates are promising ideal durable carbon support also amenable for post characterization for evaluation of hydrogen evolution reaction catalysts. Abstract : Increasing fossil fuel demands and growing concerns of global climate change have stimulated interest in the development of electrocatalysts to produce H2 as an alternative zero-emission fuel from the electrolysis of water via hydrogen evolution reaction (HER). Precious or non-precious catalysts are typically loaded on high surface area carbon materials, and these supports play a critical role in both thermodynamics and kinetics of the HER. In this paper, we evaluate the electrocatalytic activity of a molecular hydrogen evolving catalyst, diacetyl-bis(4-methyl)-3-thiosemicarbazone Ni(ii ) (Ni-ATSM), on three different carbon surfaces: glassy carbon, carbon paste and pencil graphite. The overpotential for each modified electrode was benchmarked at a current density of −10 mA cm −2 . Carbon paste electrodes showed highest overpotentials (495 mV) compared to the other electrode surfaces. Polished pencil and glassy carbon modified electrodes performed similarly ( η = 395 mV for GCE and η = 400 mV for pencil). Pencil electrodes etched in acetone overnight prior to Ni-ATSM deposition produced lowest overpotentials ( η = 354 mV). Etching results in an increase in electroactive surface area and substantial decrease in the charge transfer resistance of the graphitic interface from 275 Ω to 50 Ω, verified using electrochemical impedance spectroscopy (EIS). Our studies demonstrate pencil graphite may serve as versatile, disposable, cost effective, and reproducible electrode surface for the evaluation of heterogeneous HER catalysts. Moreover, pencils can be easily cut with table saw to generate new surface for easy characterization of the surface such as electrochemistry, imaging and spectroscopy.